Response surface methodology for aqueous two-phase system extraction: An unprecedented approach for the specific flavonoid-rich extraction of Houttuynia cordata Thunb. leaves towards acne treatment - Minh Hien Nguyen; Lan Thi Nguyen; Thien Han Nguyen Le; Trong Nghia Ngoc Chau; Yen Nhi Thi Nguyen; Tan Dat Ha; Phuoc Thuan Tran Nguyen; Thien Bao Chu; Chi Hieu Tran; Minh Tri Le (Heliyon, 2024)
Background: Houttuynia cordata Thunb. has long been widely used as a daily vegetable and traditional medicine. The flavonoid component of H. cordata has plenty of pharmacological effects, such as antibacterial, anti-inflammatory, and antioxidant. In this study, we applied the aqueous two-phase system (ATPS) combined with ultrasonic extraction for extracting H. cordata leaves. Methods: We optimized the extraction process to improve the extraction efficiency of the two flavonoids, hyperin and quercitrin, by Surface Method Response - Central Composite Design (RSM-CCD). Next, we investigated the antibacterial ability of H. cordata ATPS extract from optimal conditions against two bacterial strains, Cutibacterium acnes and Staphylococcus epidermidis. Results: The results showed that using 10% (NH4)2SO4 and 35% ethanol for ATPS extraction resulted in the highest hyperin and quercitrin contents. From the RSM-CCD results, the optimal extraction conditions were determined to be ultrasonic extraction at 50 °C for 30 min, giving results consistent with the predicted model and obtaining hyperin and quercitrin contents at 1.5681 ± 0.0114 and 4.6225 ± 0.0327 mg/g, respectively.Furthermore, ATPS extract has excellent antibacterial activity with a minimum inhibitory concentration (MIC) value of 250 μg/mL on both C. acnes and S. epidermidis. This MIC is significantly lower than the H. cordata ultrasound-assisted (UA) extract, with MICs of 1500.00 and 156.25 μg/mL on C. acnes and S. epidermidis, respectively. In addition, the results from the disk diffusion assay also showed that ATPS extraction has superior internal antibacterial activity with a zone of inhibition diameter at 250 μg/mL of 8.67 ± 1.15 and 5.00 ± 2.00 mm. Meanwhile, those of UA extract on C. acnes is 5.67 ± 1.53 mm (at 1500 μg/mL), and on S. epidermidis is 1.34 ± 0.58 mm (at 156.25 μg/mL). Conclusion: To sum up, our research highlights the potential of H. cordata ATPS extracts as the starting material for topical preparations for effectively treating acne.